2014
DOI: 10.5897/ajpp2014.4042
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial meningitis: An update review

Abstract: Bacterial meningitis is still considered serious life-threatening disease in spite of the decline in the morbidity and mortality in the last decade. The expeditious diagnosis of the disease, a prompt empiric antibiotic treatment and the proper adjunctive therapy are corner stones for the successful management of the disease. The objective of this review is to provide the health care professionals with an update of reference for bacterial meningitis diagnosis and treatment. In addition, the various types of vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Infectious meningitis can be further sub-divided to nonbacterial and bacterial (pyogenic) meningitis. Nonbacterial meningitis is typically caused by viral or fungal infections (Al Bekairy et al, 2014).…”
Section: Etiology Of Meningitismentioning
confidence: 99%
“…Infectious meningitis can be further sub-divided to nonbacterial and bacterial (pyogenic) meningitis. Nonbacterial meningitis is typically caused by viral or fungal infections (Al Bekairy et al, 2014).…”
Section: Etiology Of Meningitismentioning
confidence: 99%
“…The univariate logistic regression analysis was done to analyse four CSF criteria that were important in assessing CSF culture; these criteria include CSF protein, CSF Gram stain status, CSF glucose, and CSF appearance. The CSF was found to be cloudy, which may be due to the presence of high levels of WBCs, RBCs, bacteria and protein (21, 22). The CSF glucose ratio of less than 0.4 was more than 80% sensitive and 98% specific for diagnosis of bacterial meningitis in children of more than two months of age (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…More than 800,000 people in this area were infected, with a case fatality rate of 10%. 2 In Saudi Arabia, the epidemics of meningitis usually occur during or after Hajj and Umrah seasons, due to massive gathering of people in certain areas. Pattern evolution confirmed that 48% of meningitis cases were reported at the two holy cities, namely, Mecca and Medina.…”
Section: Introductionmentioning
confidence: 99%
“…Pattern evolution confirmed that 48% of meningitis cases were reported at the two holy cities, namely, Mecca and Medina. 2 In 2000, Indonesian pilgrims were infected by Neisseria meningitidis serogroup A and W135. Among 253 identified cases from Saudi Arabia, 93 cases were caused by N. meningitidis serogroup W135, while 60 cases were caused by N. meningitidis serogroup A. Statistically, there were nine cases caused by serogroup W135 and six cases caused by serogroup A per 100,000 population.…”
Section: Introductionmentioning
confidence: 99%